Telemedicine-Guided Cardiopulmonary Resuscitation in A COVID-19 Patient Admitted to a Field Hospital - Magalhaes, Iuri R.; Accorsi, Tarso A. D.; Scarpanti, Fernando G.; Lima, Karine De Amicis; Morbeck, Renata A.; Pedrotti, Carlos H. S.; Cordioli, Eduardo (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Telemedicine offers instrumental support in the COVID-19 pandemic, helping restructure overloaded health systems. However, there exists a paucity of evidence regarding the feasibility and aid offered by telemedical consultation during life-threatening situations. Narrative: This paper is a case report of a confirmed COVID-19 66-year-old female admitted to a field hospital who evolved with an unstable condition and suffered a cardiac arrest. All data were collected through a retrospective analysis of the medical records and relevant information is presented. General practitioners assisted the patient during cardiac arrest, helped remotely by a cardiologist, who orientated the ACLS (Advanced Cardiovascular Life Support) protocol review. Discussion: A telemedicine-guided tension pneumothorax diagnosis was made, allowing timely drainage. The patient recovered through spontaneous circulation; post-cardiac arrest management was also remotely guided and there was progressive recovery. This case demonstrates that low-cost and easy-access specialist teleconsultation may be feasible and effective to improve protocol-adherence even in extreme situations and can be expanded in several scenarios. <gdiv></gdiv>